Ebola-GP DNA Prime rAd5-GP Boost: Influence of Prime Frequency and Prime/Boost Time Interval on the Immune Response in Non-human Primates - Marcus, Hadar; Thompson, Emily; Zhou, Yan; Bailey, Michael; Donaldson, Mitzi M.; Stanley, Daphne A.; Asiedu, Clement; Foulds, Kathryn E.; Roederer, Mario; Moliva, Juan I.; Sullivan, Nancy J. (Frontiers in Immunology, 2021)
Heterologous prime-boost immunization regimens are a common strategy for many vaccines. DNA prime rAd5-GP boost immunization has been demonstrated to protect nonhuman primates against a lethal challenge of Ebola virus, a pathogen that causes fatal hemorrhagic disease in humans. This protection correlates with antibody responses and is also associated with IFN+ TNF+ double positive CD8+ T-cells. In this study, we compared single DNA vs. multiple DNA prime immunizations, and short versus long time intervals between the DNA prime and the rAd5 boost to evaluate the impact of these different prime-boost strategies on vaccine-induced humoral and cellular responses in nonhuman primates. We demonstrated that DNA/rAd5 prime-boost strategies can be tailored to induce either CD4+ T-cell or CD8+ T-cell dominant responses while maintaining a high magnitude antibody response. Additionally, a single DNA prime immunization generated a stable memory response that could be boosted by rAd5 three years later. These results suggest DNA/rAd5 prime-boost provides a flexible platform that can be fine-tuned to generate desirable T-cell memory responses.